1980
DOI: 10.2754/avb198049010053
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E and C in the Blood Plasma of Cows and their Calves Fed from Buckets

Abstract: Bouda J., P. Jagos, R. Dvorak, J. Ondrova: Vitamin E and C in the Blood Plasma of Cows and their Calves Fedfrom Buckets. Acta vet. Brno, 49,1980: 53-58.The vitamin E and C levels were studied in the blood plasma and colostrum of 40 cows and in the blood plasma of their calves until the age of 3 months. The assays were made in winter. The vitamin E levels prior to and after parturition did not show appreciable differences while the vitamin C levels prior to parturition were significantly lower. The vitamin E co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 6 publications
1
15
0
1
Order By: Relevance
“…It was, however, lower (P < 0.01) than the variation within days, which is in agreement with the study reported by Bouda et al (1980). It is suggested that in the calf, ascorbic acid concentration is an indication of its current metabolic situation and, therefore, subject to greater fluctuation.…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations
“…It was, however, lower (P < 0.01) than the variation within days, which is in agreement with the study reported by Bouda et al (1980). It is suggested that in the calf, ascorbic acid concentration is an indication of its current metabolic situation and, therefore, subject to greater fluctuation.…”
Section: Introductionsupporting
confidence: 91%
“…It is probable that the ascorbic acid synthesizing ability is missing or is insufficient during the early postnatal period (Palludan and Wegger, 1984). This assumption is supported by Smirnov (1962) and Bouda et al (1980). Therefore, some form of vitamin C supplementation may be beneficial to newborn calves to enhance resistance to infectious diseases.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Os bezerros não sintetizam ácido ascórbico até aproximadamente 4 meses após o nascimento. Os maiores níveis plasmáticos são detectados no dia do nascimento, antes da amamentação, diminuindo nas duas semanas seguintes, quando então se estabiliza devido ao início da síntese endógena (LUNDQUIST e PHILLIPS, 1942;BOUDA et al 1980). Nos animais dependentes de ácido ascórbico de origem dietética, a absorção ocorre de forma similar à dos monossacarídeos, através de transporte ativo sódio-dependente, no intestino delgado (RIVERS, 1987).…”
Section: Biossíntese E Metabolismounclassified